Mergers, acquisitions, and corporate restructurings - Gaughan, Patrick A. (Hoboken, N.J. : Wiley, 2007)
The book carefully analyzes the strategies and motives that inspire Mergers & Acquisitions, the laws and rules that govern the field, as well as the offensive and defensive techniques of hostile acquisitions.
Includes bibliographical references and index.
rua 26/02/15
Loans
Keywords: Consolidation and merger of corporations; Corporate reorganizations; Mergers and acquisitions